Cohort differences in changing attitudes toward marriage in South Korea, 1998–2014: an age-period-cohort-detrended model. Issue 3 (2nd September 2019) - Lee, Yoonjoo
ABSTRACT: Although the proportion of people who agree with the necessity of marriage has continuously declined over recent decades in South Korea, the contribution of cohort changes in attitudes toward marriage has not been examined. Using a descriptive age-period-cohort-detrended model and nationally representative cross-sectional data pooled from 1998 to 2014 ( N  = 193, 610), this study investigates unique cohort effects and variation by gender. The results show that cohorts born in the 1960s and 1970s are less likely to see marriage as imperative than their previous and following cohorts. Such cohort effects are more pronounced in women than men. These findings suggest that cohorts whose formative experiences contribute to the liberalisation of attitudes tend to have liberal attitudes toward marriage.